(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In order to learn more about how the Nd: YAG laser affects enamel ,dentin, and pulp, Scholarly , articles were acquired from three distinct sources.in those study , the three tissues or a portion of them were exposed to the Nd:YAG radiation .beam of YAG laser, largely in vitro, and the results were later seen. The hardness and acid resistance The hardness and acid resistace of enamel increased, making the laser a realistic choice to offer some defense against tooth cavities. Moreover, the roughness increased. Some laser settings produced a surface that looked like glass. Surface alterations resembling acid etching were achieved by various lasing settings. Dentinal tubules were blocked and its permeability decreased. This could account for the decrease in dentin hypersensitivity following lasing. Both enamel and dentin developed cracks and microfissures as a result of prolonged exposure and increased beam energy. A study revealed that although the laser has been used to remove the smear layer from dentin, it may not be efficient. The pulp got pain relief brought on by laser. The laser demonstrated that it can enhance pulp local blood flow.